Hematological profile of wild-captured Indian Flying Fox (Pteropus giganteus) in Bangladesh - Hossain, MB; Islam, MN; Yasin, MG; Hassan, MM; Islam, SKMA; Khan, SA (International Journal of Natural Sciences, 2016)
The current study was conducted to examine hematological parameters of large frugivorous bats under the class mammalian. Ninety (90) clinically healthy large frugivorous bats were captured and anesthetized for blood collection from brachial vein. Captured bats were divided into three groups based on different criteria such as sex, age and body condition score. Red blood cell (RBC) count, hemoglobin (Hb), hematocrits (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration(MCHC), red cell distribution width (RDWs), white blood cell (WBC) count, platelets (PLT), mean platelet volume (MPV), platelet distribution width (PDW) were determined by automated hematology analyzer and erythrocyte sedimentation rate (ESR) was determined manually. RBC and MCV values were found significantly (p < 0.05) higher in male bats. On the other hand, the RBC count, HCT, Hb, RDWs and PLT were significantly (p < 0.05) higher in adults than in juveniles bats. Among the health state RBC, HCT and PLT values were significantly (p < 0.05) higher in good-health bats. However, some values were varied in different groups, but they were not statistically significant (p >0.05). The values from this study can be used to create reference of hematological profile of bat found in Indian subcontinent, and can make up the first comprehensive hematological study for this highly endangered species. International Journal of Natural Sciences (2013), 3(1-4) 12-17